Fuzzy control strategy for a compound energy system for an urban rail train based on the required power. (15th October 2020) - Wang, Xiaokan; Wang, Qiong
Highlights: Compound energy system of metro with lithium battery and supercapacitor. Fuzzy energy control method with multiple inputs considering power demand. Prolong lithium battery life and meet power demand of real train. Improve the stability and comfort of train operation. Recover the braking energy and improve the system utilization rate. Abstract: In this paper, a fuzzy energy control method with multiple inputs is proposed that considers the power demand of the system. It targets the problem of the power distribution of the combined power supply of the supercapacitor and lithium battery in composite energy storage systems of urban rail trains. The composite energy control system is modeled and simulated by using the required power of the train, the state of charge for lithium battery and supercapacitor as the inputs and the power distribution coefficient of the lithium battery as the output in the fuzzy controller. Simulation results show that the fuzzy controller can distribute energy well, satisfy the power demand of real train operation, reduce the impact of large current on the lithium battery, and improve the cycle utilization times of the lithium battery, which is conducive to improving the stability and comfort of train operation.